Histopatologia do intestino de Pseudoplatystoma fasciatum (osteichthyes, pimelodidae) parasitados com cestodas proteocefalídeos e nematodas - de Campos, Cristiane Meldau (2009)
This work describes intestine histopathology of Pseudoplatystoma fasciatum infected by endohelminths. Nineteen specimens were caught from Aquidauna River, Mato Grosso do Sul State, in October 2005 and submitted to necropsy, when intestine of each specimen was fixed with AFA solution during 12 h. Soon after, samples were immersed in buffered formalin and 24 h after, transferred to alcohol 70%. Study of histology sections was made to 5; m and stained with haematoxylin and eosin. It showed structures displaying helminths encapsulated by connective tissue in intestinal muscle with fibroplasy in several stages of capsule development. Were observed focus of necrosis in intestinal mucous and sub-mucous and helminthes cut obliquely in intestinal lumen. In addition, there was discreet mucous desquamation, associated to basal membrane thickness.